Cognitive results after a FINGER‐like one‐year randomized controlled multidomain intervention: The GOIZ ZAINDU pilot project: Prevention (nonpharmacological) / Multidomain. (7th December 2020) - Ecay, Mirian; Tainta, Mikel; Mugica, Justo; Arriba, Maria; Ros, Naia; Barandiaran, Myriam; Iriondo, Ane; Garcia‐Sebastian, Maite; Estanga, Ainara; Aurtenetxe, Sara; Saldias, Jon; Clerigue, Montserrat; et al.
Abstract: Background: Previous trials in Europe (FINGER, MAPT and PreDIVA) have shown that interventions on risk and protective factors represent a window of opportunity for dementia prevention, especially in participants with increased risk. To fully understand the potential impact of these interventions, their feasibility and efficacy needs to be explored in contexts worldwide. GOIZ ZAINDU ("caring early" in Basque language) is a pilot study to adapt FINGER methodology in Southern Europe with the aim to evaluate the feasibility of a lifestyle intervention program in this cultural and social context. An additional exploratory aim is to assess the efficacy of the intervention on cognition. Method: GOIZ ZAINDU is a one year controlled, randomized, multimodal intervention. Inclusion criteria were: age 60+; CAIDE dementia risk score of 6 points or higher; no dementia; and below‐than‐expected cognitive performance in at least one of three brief cognitive screening tests. Cognitive status (MCI or normal) and age were accounted for randomization to a multidomain intervention (MI) or to Regular Health Advice (RHA). MI includes cardiovascular risk control, nutritional counseling, physical activity program, and cognitive training. Cognitive outcomes include the modified Neuropsychological Test Battery (mNTB) composite score change, and domain Z score change for executive function, processing speed, and memory. Mixed‐effects regression models with maximum likelihood estimation to analyze change in cognitive scores as a function of randomization group, time and groupxtime interaction will be performed. Result: 125 participants were recruited. 64 people were assigned to MI and 61 to RHA. The study started in June 2018, last patient first visit was in March 2019. Up to date 94 participants have completed the study that will end in April 2020. Exploratory results of the efficacy analysis of the intervention on cognition change will be presented. Conclusion: The GOIZ‐ZAINDU study has proved that the FINGER methodology is adaptable and feasible in a different socio‐cultural environment. Exploratory efficacy results will support the design of the large‐scale efficacy FINGER‐like trial in the Basque Country.